(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Infodemics has been considered as the double-edged sword, a perspectivity influencing the lives of common man. Human life has been affected by it, which caused derailment of normal functionality of human life. It has been considered as the blend of information and misinformation that affected the emotional status of the human beings affected by social media. In order to cope up with the rumours and myths, management of infodemics had to be dealt with alternate strategies like identifying and segregating the information from misinformation, identifying the mis endeavours of the state players and understanding the origin and the spread of the misinformation. It also dealt with the verification and spread of credible information and identifying the lapses in regards to the spread of information through proper sources and channels. To conclude, the devious nature of infodemics can throw the world into turmoil or help restore peace and serenity if is handled in proper method.